2023
DOI: 10.1186/s12909-023-04177-5
|View full text |Cite
|
Sign up to set email alerts
|

The framework of Systematic Assessment for Resilience (SAR): development and validation

Abstract: Background Burnout and depression among health professions education (HPE) students continue to rise, leading to unwanted effects that ultimately jeopardise optimal medical care and patient health. Promoting the resilience of medical students is one solution to this issue. Several interventions have been implemented to foster resilience, but they focus on aspects other than the primary cause: the assessment system. The purpose of this study is to develop a framework to promote resilience in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Similarly, Clipa et al [ 16 ] found that students’ resilience increases when they practice formative assessment, which reduces test anxiety. Although both studies have the same findings, the intervention proposed in the current study was developed based on a solid evidence-based framework [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Clipa et al [ 16 ] found that students’ resilience increases when they practice formative assessment, which reduces test anxiety. Although both studies have the same findings, the intervention proposed in the current study was developed based on a solid evidence-based framework [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their recent research, Wadi et al developed a framework for fostering resilience through the process of student assessment [ 31 ]. This framework is called the Systematic Assessment for Resilience (SAR) framework and encompasses numerous guidelines for fostering resilience and enhancing its four constructs: (1) self-control, in which students should be able to govern themselves and face adversity; (2) management, which describes the students’ ability to use available resources effectively to overcome obstacles; (3) engagement, which highlights the students’ ability to be involved and committed to pursuing challenges with perseverance; and (4) growth, which reflects the students’ ongoing development to face future challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation